The Challenges of PT PLN (Persero) in Earning Operational Profit - Rusdy, Hildayani; Laba, Abdul Rakhman; Sobarsyah, Muhammad (Economics and Business Journal (ECBIS), 2023)
This research aims to explain the challenges PT PLN (Persero) faced in managing accounts receivable and improving profitability. The research method used is qualitative, with data collection techniques through library research. The data used are secondary data obtained from books, journals, documents, official websites, or reports on the issues under investigation. The data analysis technique employed is a qualitative analysis using quantitative data as support. The research findings indicate that PLN encounters various challenges in managing accounts receivable and enhancing business profits, such as regulatory issues, competition, and technological changes. Therefore, PLN must develop appropriate strategies to address these challenges and attain a stable and continuously increasing business profit.